THE PROBLEM OF THE ARTISTIC EXPRESSION OF ARTIFICIAL INTELLIGENCE AND HUMAN EMOTIONS IN CONTEMPORARY UZBEK POETRY (Scientific journal of the Fergana State University, 2026)
This article analyzes the problem of artistic expression of human emotions in the era of technocivilization and artificial intelligence in contemporary Uzbek poetry. It explores poetic interpretations of digital thinking, virtual life, and the symbolic representations of robots and digital codes, highlighting the spiritual conflicts between artificial consciousness and the human heart. The study also examines how young poets perceive technological modernism and develop new forms of lyricism under the influence of digital environments and social media culture.